THE USE OF DIARY WRITING TO IMPROVE STUDENTS RECOUNT TEXT - Hermawan, Uray Ryan; Sada, Clarry; Rezeki, Yanti Sri (FKIP - Universitas Tanjungpura, 2020)
The research was aimed to investigate the use of diary writing to overcome students’ problem in writing recount texts. The problems include writing a recount text in chronological order, writing correct verb changes and developing ideas. Classroom action research was conducted by applying diary as the technique to help students overcome their problem. There were two cycles conducted in this research. The data were taken from the students’ individual score, observation checklist, and field notes. The result showed that teaching writing through diary writing improved students’ writing recount text. Referring to the research findings, the data showed that diary writing improved students’ recount text, as seen in their score. These in terms of score, students’ improved from 71.96 to 76.03 and improving the motivation to the students which makes them eager to write also makes the teaching learning process better. In conclusions, students’ writing recount text of the tenth grade students of class IPS 1 of SMAN 4 Sungai Raya in academic year 2018/2019 improved by using diary.